(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2003)
The origin of late Permian olistoliths found in the Glypia Cenozoic flysch must be seeked in regions located to the east of the Parnon Mountain and in units that were more internal to Pindos Unit, especially in the islets of Karavia in the Argolis Gulf, and the Episkopi Formation in Hydra Island, that display probably the largest outcrops of this age. The most interesting olistolith is a bioclastic grainstone. It yields about forty taxa of algae, microproblematica, smaller foraminifers and fusulinids, that are briefly described. Three markers generally not co-occurring are locally associated: Paradunbarula (Shindella) shindensis, Hemigordiopsis cf. luquensis and Colaniella aff. minima. The age of the Paradunbarula (Shindella) biozone is most probably late Wuchiapingian/Dzhulfian, although other datings have been proposed from late Capitanian to late Changhsingian. Due to this dating of the Shindella zone, the coexistence of the first Colaniella with the last Hemigordiopsis are not late Capitanian/Midian in age, but late Wuchiapingian. The similarities of the Greek microfauna with that of South China and southeastern Pamirs, are incompatible with a larger Paleotethys but support the paleogeographic reconstructions which indicate a close location of these geographic units (Pangea B).